Pemanfaatan Teknologi Augmented Reality (AR) Sederhana Untuk Meningkatkan Engagement Pelanggan Pada Program Pemasaran UMKM - Hermawan Honggo Widagdo; Ahmad Nugroho; Gati Zulfikar (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study explores the utilization of simple Augmented Reality (AR) technology to enhance customer engagement in the marketing programs of small and medium-sized enterprises (SMEs), specifically focusing on Anna Rental Perlengkapan Bayi in Semarang. The research employs an experimental design, developing and evaluating an AR-based information system prototype. Data collection methods include structured interviews, direct observations, and analysis of Instagram post performance. Results indicate a significant increase in customer engagement with AR content, showing an increase from fewer than 100 viewers for regular content to approximately >200 viewers for AR content, with 5% of these engaging further by clicking the AR link and 2% proceeding with a call-to-action. These findings align with existing theories on the effectiveness of interactive technologies in marketing. The study concludes that AR technology can substantially enhance customer engagement and suggests that SMEs adopt such technologies for improved marketing outcomes. Practical implications highlight the need for training and support for SMEs to implement AR effectively. This research provides a foundation for further studies on AR applications in SME marketing strategies in Indonesia.